2022
DOI: 10.3390/jcm11123263
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia after Perinatal Asphyxia Does Not Affect Genes Responsible for Amyloid Production in Neonatal Peripheral Lymphocytes

Abstract: In this study, the expression of the genes of the amyloid protein precursor, β-secretase, presenilin 1 and 2 by RT-PCR in the lymphocytes of newborns after perinatal asphyxia and perinatal asphyxia treated with hypothermia was analyzed at the age of 15–21 days. The relative quantification of Alzheimer’s-disease-related genes was first performed by comparing the peripheral lymphocytes of non-asphyxia control versus those with asphyxia or asphyxia with hypothermia. In the newborns who had perinatal asphyxia, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 48 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…There is increasing evidence that the neuropathology induced in the neonate’s brain during and after perinatal asphyxia is similar to that of adult neurodegenerative diseases, such as Alzheimer’s disease [ 13 , 42 , 44 , 45 , 46 , 49 ]. Additionally, one study found elevated plasma levels of tau protein following asphyxia on days 3 and 7 after birth [ 48 ].…”
Section: Brain Neuropathology After Perinatal Asphyxiamentioning
confidence: 99%
See 3 more Smart Citations
“…There is increasing evidence that the neuropathology induced in the neonate’s brain during and after perinatal asphyxia is similar to that of adult neurodegenerative diseases, such as Alzheimer’s disease [ 13 , 42 , 44 , 45 , 46 , 49 ]. Additionally, one study found elevated plasma levels of tau protein following asphyxia on days 3 and 7 after birth [ 48 ].…”
Section: Brain Neuropathology After Perinatal Asphyxiamentioning
confidence: 99%
“…Additionally, it has been noticed that newborns after perinatal asphyxia, untreated or treated with hypothermia, presented identical changes in gene expression related to the processing of the amyloid protein precursor in lymphocytes [ 49 ]. Knowing about the possibility of passing lymphocytes after perinatal asphyxia to the brain, our data suggest an additional role of lymphocytes in progressive neurodegeneration with amyloid deposition, despite hypothermic treatment of neonates after perinatal asphyxia.…”
Section: Brain Neuropathology After Perinatal Asphyxiamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is assumed that hypoxia in the perinatal period may be a factor triggering the development of Alzheimer's disease in adulthood [5]. Studies have shown changes in the expression of the presenilin 1 and 2 and amyloid protein precursor and β-secretase genes in neonates after asphyxia, similar to those observed in Alzheimer's disease [6].…”
Section: Introduction and Objectivementioning
confidence: 96%